Genome‐wide association and gene validation studies for early root vigour to improve direct seeding of rice. (9th August 2018) - Wang, Fanmiao; Longkumer, Toshisangba; Catausan, Sheryl C.; Calumpang, Carla Lenore F.; Tarun, Jeshurun A.; Cattin‐Ortola, Jerome; Ishizaki, Takuma; Pariasca Tanaka, Juan; Rose, Terry; Wissuwa, Matthias; Kretzschmar, Tobias
Abstract: Elucidation of the genetic control of rice seedling vigour is now paramount with global shifts towards direct seeding of rice and the consequent demand for early vigour traits in breeding programmes. In a genome‐wide association study using an indica‐predominant diversity panel, we identified quantitative trait loci (QTLs) for root length and root number in rice seedlings. Among the identified QTLs, one QTL for lateral root number on chromosome 11, qTIPS‐11, was associated with a 32.4% increase in lateral root number. The locus was validated in independent backgrounds, and a predicted glycosyl hydrolase, TIPS‐11‐9, was identified as the causal gene for observed phenotypic differences. TIPS‐11‐9 was differentially expressed in emerging lateral roots of contrasting qTIPS‐11 haplotypes, which was likely due to differences in cis ‐regulatory elements and auxin responsiveness. Abolishment of Tips‐11‐9 function through T‐DNA insertion in a qTIPS‐11 ‐positive background resulted in a reduction of lateral root number, which negatively affected biomass accumulation, particularly under phosphorous‐limiting conditions. Marker‐assisted introgression of qTIPS‐11 into modern indica varieties will aid in the generation of varieties adapted to direct seeding and thus facilitate the adoption of direct seeding practices in tropical Asia.